MENGESTIMASI EFEK PENGETAHUAN DAN MOTIVASI INVESTASI TERHADAP KEPUTUSAN PEMBELIAN SAHAM SYARIAH - hesi eka puteri; Mela Indah Permata Sari (universitas teuku umar, 2022)
AbstractThe commitment of investors to invest their funds in Islamic stock instruments is influenced by various rational considerations because the decision to invest in stocks is closely related to risk and return. This study aims to analyze the effect of knowledge and investment motivation on purchasing decisions of sharia stock by society in the city of Bukittinggi. This type of research is a field research with a quantitative approach. This research picks up Bukittinggi as a sampling area with a sample of 100 Sharia stock investors, which were selected purposively. The results of the study prove that there is a significant positive influence of knowledge and investment motivation on sharia share purchase decisions with a contribution of 63.8%, while the remaining 36.2% is influenced by other variables outside the model. The higher the level of knowledge and investment motivation, the greater the decision to purchase sharia stock. This finding convinces potential investors and policy makers of the importance of stock knowledge and investment motivation in order to avoid risk. This study can be an important reference regarding the need for appropriate socialization and marketing strategies based on consumer behavior in developing market share of Islamic stocks in the secondary market.Keywords: Investment Knowledge, Investment Motivation, Sharia Stock Purchase Decision